Chromosome 1 variants associated with decreased HIV set-point viral load correlate with PRKAB2 expression changes - Tough, Riley H.; McLaren, Paul J. (Frontiers in Genetics, 2025)
A previous study investigated a genomic region on chromosome 1 associated with reduced human immunodeficiency virus type 1 (HIV) set-point viral load, implicating CHD1L as a novel HIV inhibitory factor. However, given that regulatory variants can influence expression of multiple nearby genes, further work is necessary to determine the impact of genetic variants on other genes in the region. This study evaluates the potential for genetic regulation of PRKAB2, a gene located upstream of CHD1L and encoding the β2 regulatory subunit of the AMPK complex, and for downstream impacts on HIV pathogenesis. Using genotype and gene expression data from the Gene Expression Omnibus repository and Genotype-Tissue Expression database, we observed cell-type-specific correlations between CHD1L and PRKAB2 expression, with a strong positive association in whole blood and negative correlation in monocytes. Notably, we found that individuals with HIV set-point viral load associated variants exhibited significantly reduced PRKAB2 expression in imputed whole blood models and ex vivo monocytes. Functional analyses using PRKAB2−/− induced pluripotent stem cells suggest that PRKAB2 loss-of-function may influence CHD1L expression, and genes regulating cytokine activity, growth factor signaling, and pluripotency pathways associated with HIV infection. These results suggest that gene expression changes driven by HIV set-point viral load associated variants in the chromosome 1 impact multiple genes and, by influencing expression of PRKAB2, may result in altered expression of critical immune signaling processes. These findings advance our understanding of the contribution of host genetics on HIV pathogenesis and identifies new targets for ex vivo functional studies.